Usefulness of applying research reporting guidelines as Writing Aid software: a crossover randomised controlled trial - Dana Hawwash; Melissa K Sharp; Alemayehu Argaw; Patrick Kolsteren; Carl Lachat (BMJ Open)
Objectives To assess the intention of using a Writing Aid software, which integrates four research reporting guidelines (Consolidated Standards of Reporting Trials, Preferred Reporting Items for Systematic Reviews and Meta-Analyses, Strengtheningthe Reporting of Observational Studies in Epidemiology and STrengtheningthe Reporting of Observational Studies in Epidemiology-nutritional epidemiology) and their Elaboration & Explanation (E&E) documents during the write-up of research in Microsoft Word compared with current practices.Design Two-arms crossover randomised controlled trial with no blinding and no washout period.Setting Face-to-face or online sessions.Participants 54 (28 in arm 1 and 26 in arm 2) doctoral and postdoctoral researchers.Interventions Reporting guidelines and their E&E document were randomly administered as Writing Aid or as Word documents in a single 30 min to 1 hour session, with a short break before crossing over to the other study intervention.Primary and secondary outcomes Using the Technology Acceptance Model, we assessed the primary outcome: the difference in the mean of intention of use; and secondary outcomes: the difference in mean perceived ease of use and perceived usefulness. The three outcomes were measured using questions with a 7-point Likert-scale. Secondary analysis using structural equation modelling (SEM) was applied to explore the relationships between the outcomes.Results No significant difference in reported intention of use (mean difference and 95% CI 0.25 (–0.05 to 0.55), p=0.10), and perceived usefulness (mean difference and 95% CI 0.19 (–0.04 to 0.41), p=0.10). The Writing Aid performed significantly better than the word document on researchers’ perceived ease of use (mean difference and 95% CI 0.59 (0.29 to 0.89), p<0.001). In the SEM analysis, participants’ intention of using the tools was indirectly affected by perceived ease of use (beta 0.53 p=0.002).Conclusions Despite no significant difference in the intention of use between the tools, administering reporting guidelines as Writing Aid is perceived as easier to use, offering a possibility to further explore its applicability to enhance reporting adherence.